Adjusting on-scene CPR duration based on transport time interval in out-of-hospital cardiac arrest: a nationwide multicenter study - Daseul Kim; Jae Yong Yu; Minha Kim; Gun Tak Lee; Sang Do Shin; Sung Yeon Hwang; Daun Jeong (Scientific Reports)
Abstract The optimal duration of on-scene cardiopulmonary resuscitation (CPR) for out-of-hospital cardiac arrest (OHCA) patients remains uncertain. Determining this critical time period requires outweighing the potential risks associated with intra-arrest transport while minimizing delays in accessing definitive hospital-based treatments. This study evaluated the association between on-scene CPR duration and 30-day neurologically favorable survival based on the transport time interval (TTI) in patients with OHCA. We retrospectively analyzed data from the Korean Cardiac Arrest Research Consortium registry of OHCA, comprising 65 participating hospitals in South Korea, between October 2015 and December 2021. We categorized the patients into Short-TTI (TTI < 10 min) and Long-TTI (TTI ≥ 10 min) groups. Differences in clinical features were adjusted for using propensity score matching (PSM) for TTI. The primary outcome was a 30-day neurologically favorable outcome, defined as cerebral performance category 1 or 2. Multivariable logistic regression was used to determine the variables associated with clinical outcomes. A generalized additive model based on a restricted cubic spline smooth function was utilized to infer the optimal cutoff point for on-scene CPR duration. Of the 6,345 patients, 5,844 PSM pairings were created (Short-TTI: 2,922; Long-TTI: 2,922). The primary outcome was achieved in 7.4% and 9.8% of the patients in Short-TTI and Long-TTI groups, respectively (p = 0.001). Increased on-scene CPR duration was associated with decreased neurologically favorable survival (adjusted odds ratio, 0.94; 95% confidence interval, 0.92–0.96). The optimal on-scene CPR durations in the overall PSM, Short-TTI, and Long-TTI groups were 5.1, 0, and 5.0 min, respectively. An adjusted on-scene CPR duration based on expected transport duration may be beneficial for favorable clinical outcomes in patients with OHCA.